Guillain–Barre syndrome outbreak in Peru: Association with polymorphisms in IL-17, ICAM1, and CD1 - Jaramillo-Valverde, Luis (2019)
Background: Guillain–Barre Syndrome (GBS) is considered a complex disorder with significant environmental effect and genetic susceptibility. Genetic polymorphisms in CD1E, CD1A, IL-17, and/or ICAM1 had been proposed as susceptibility genetic variants for GBS mainly in Caucasian population. This study explores the association between selected polymorphisms in these genes and GBS susceptibility in confirmed GBS cases reported in mestizo population from northern Peru during the most recent GBS outbreak of May 2018. Methods: A total of nine nonrelated cases and 11 controls were sequenced for the polymorphic regions of CD1A, CD1E, IL-17, and ICAM1. Results: We found a significant protective association between heterozygous GA genotype in ICAM1 (241Gly/Arg) and GBS (p '.047). IL-17 was monomorphic in both controls and patients. No significant differences were found in the frequency of SNPs in CD1A and CD1E between the group with GBS patients and healthy controls. Conclusion: ICAM1 polymorphisms might be considered as potential genetic markers of GBS susceptibility. Further studies with larger sample size will be required to validate these findings.